VISUAL CONSISTENCY MANAGEMENT SYSTEM: METHODOLOGY FOR CONTROLLING STYLISTIC UNITY AT ALL STAGES OF VIDEO PRODUCTION - Neryanov, Pavlo (European Journal of Interdisciplinary Issues, 2025)
The article explores differentiated approaches to ensuring visual consistency and stylistic unity at all stages of video production in the context of modern generative technologies. The relevance of the study is due to the rapid development of video generation based on text and image queries, which requires new approaches to controlling the quality and stability of the composition. The research methodology consists in applying a complex of general scientific and special methods, in particular theoretical analysis, modeling, system-structural approach and comparative analysis, which allowed us to investigate architectural solutions of generative models (T2V and I2V) for ensuring visual consistency, composition stability and controllability of the video sequence. Results. The study found that ensuring visual consistency is a key aspect of modern video production, covering all stages of content creation - from pre-production to post-production. The study found that the greatest potential for increasing the stylistic unity of video is provided by the latest methods of video generation, in particular through the use of artificial intelligence algorithms based on generative adversarial networks and diffusion models. It was found that methods that include the use of the first frame as a reference element for the entire video sequence significantly increase the level of composition stability, but they still demonstrate shortcomings in the accuracy of local detail reproduction and smoothness of movement. It was determined that one of the most effective approaches is the integration of spatiotemporal conditioning, in particular through the use of the ConsistI2V model, which provides a high level of stylistic consistency based on a diffusion approach, which allows to eliminate the problem of visual artifacts and ensure smooth transitions between frames, while maintaining compositional integrity. Conclusions. Based on the conducted research, it was established that the visual consistency management system is an important tool for ensuring stylistic unity at all stages of video production, and the implementation of stylistic unity control contributes to improving the quality of video content, preserving a single visual style and ensuring effective communication with the audience. Based on the conducted research, we can note that the visual consistency control system has the potential to increase the competitiveness of video products in the market and optimize the content production process.